Assessment of cloud condensation nucleus activation of urban aerosol particles with different hygroscopicity and the application to the cloud parcel model. Issue 6 (27th March 2014) - Kawana, Kaori; Kuba, Naomi; Mochida, Michihiro
Abstract Size‐resolved measurements of the ratios of cloud condensation nuclei (CCN) to condensation nuclei for particles with different hygroscopic growth factors (g) and distributions of g at 85% relative humidity were performed for urban aerosols over Nagoya, Japan. The CCN efficiency spectra of less hygroscopic particles (g of 1.0 and 1.1) were very different from those of more hygroscopic particles (g of 1.25 and 1.4). While the differences between the CCN activation diameters predicted from g (dact, g85) and those measured (dact, CCN) were within 12% for more hygroscopic particles, the differences were larger (16%–41%) for less hygroscopic particles. Possible causes of this included surface tension reduction, the dependence of κ on the concentration of the solution, the existence of sparingly soluble materials, and asphericity of particles. The number concentrations of CCN (NCCN) and cloud droplets (Ncd) and the effective radius of cloud droplets (Reff) were estimated from the distributions of g using a cloud parcel model. The influences of the differences between dact, g85 and dact, CCN and the existence of CCN‐inactive particles on the model assessment were small. With high updraft velocity, incorporating both less and more hygroscopic particles into the model led to substantial increases in NCCN and Ncd and a decrease in Reff as compared to the hypothetical cases that only more hygroscopic particles were present. The results indicated that less hygroscopic particles significantly contribute to cloud droplet formation and assessments of g distributions are useful in this regard.